Pengembangan Media Pembelajaran Pop Up Book Pelajaran Matematika di Sekolah Dasar - Lutfiyyah Indah Permata Sari; Ramanata Disurya; Tanzimah (Universitas Muhammadiyah Kuningan, 2025)
This research aims to produce Pop Up Book learning media for Mathematics learning that is valid, practical and effective/has potential effects. The model used in the research is the ADDIE model (Analyze, Design, Development, Implementation and Evaluation). The results of data analysis show that the Pop Up Book developed is in the